2014
DOI: 10.1016/j.antiviral.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronically FIV-infected cats with suberoylanilide hydroxamic acid

Abstract: Feline immunodeficiency virus (FIV) is a naturally-occurring, large animal model of lentiviral-induced immunodeficiency syndrome, and has been used as a model of HIV pathogenesis and therapeutic interventions. HIV reservoirs in the form of latent virus remain the primary roadblock to viral eradication and cure, and FIV has been previously established an animal model of lentiviral latency. The goal of this study was to determine whether administration of the histone deacetylase inhibitor (HDACi) suberoylanilide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…During this study period, plasma vRNA was not detected within the limits of the real-time PCR assay for any of the FIV-infected and uninfected cats, consistent with our previous observations [ 10 , 11 , 18 ]. Proviral DNA loads for unfractionated PBMCs and PLN-derived leukocytes, as well as from blood and PLN enriched CD4+ and CD21+ populations were determined by real-time PCR.…”
Section: Resultssupporting
confidence: 92%
“…During this study period, plasma vRNA was not detected within the limits of the real-time PCR assay for any of the FIV-infected and uninfected cats, consistent with our previous observations [ 10 , 11 , 18 ]. Proviral DNA loads for unfractionated PBMCs and PLN-derived leukocytes, as well as from blood and PLN enriched CD4+ and CD21+ populations were determined by real-time PCR.…”
Section: Resultssupporting
confidence: 92%
“…This report also revealed that latent infection was characterized by the association of the FIV 5¢ long terminal repeat (LTR) promoter with host histone proteins that were hypermethylated and deacetylated, consistent with a condensed chromatin state [123]. Subsequent reports demonstrated that latently FIV-infected cells could be reactivated ex vivo through the administration of histone deacetylase inhibitors suberoylanilide hydroxamic acid, valproic acid, trichostatin A, and sodium butyrate (NaB) and a histone methyltransferase inhibitor 3-deazanoplanocin A [124,125]. Similar findings were reported in two studies by Tadafumi and Chan who used histone deacytelase NaB and protein kinase-C inhibitors, respectively, to reverse FIV latency [120,126].…”
Section: Fiv Latencymentioning
confidence: 95%
“…Though logical, experience to date has not fulfilled these expectations. Specifically, studies have demonstrated that: only a small fraction of proviruses present in resting CD4 + T cells are reactivated by a single round of HDACi treatment in vitro [ 53 ]; reactivation of infected, resting CD4 + T cells by vorinostat did not result in viral CPE-mediated cell death [ 42 ]; impairment of host HIV-specific CTLs’ functions is specifically associated with immunodeficiency characteristic to HIV infection even in treated patients [ 54 ]; viral clearance by the CTLs only occurs in elite controllers [ 55 ]; the effect of various LRAs on latently infected cells, both in vivo and ex vivo , is highly variable [ 45 , 56 , 57 ]; in vitro treatment of cells with HDACi can impair CTL function [ 51 ]; and, finally, much of the virus present in latently infected cells in individuals that started ART in the chronic phase of infection contains escape mutations for immunodominant epitopes [ 58 ].…”
Section: Introductionmentioning
confidence: 99%